Energy : resources, technologies and the environment - Ngo, Christian; Bigot, Bernard; Hamand, Jeremy; The Institution of Engineering and Technology (London : Institution of Engineering and Technology, 2010)
This book is aimed at students and professionals as well as anyone interested in having a global vision and perspective on energy.
Basic concepts -- Fossil fuels -- Renewable energies -- Nuclear energy -- Utilisation and storage -- Energy and the environment -- Future prospects.
Includes bibliographical references and index.
Keywords: Power resources; Power resources